2014
DOI: 10.1080/13632752.2014.947096
|View full text |Cite
|
Sign up to set email alerts
|

Critical psychologies of disability: boundaries, borders and bodies in the lives of disabled children

Abstract: Attending to the ways in which bodies and subjectivities are constituted in social environments is not simply a concern of social geographers but an emerging interest in critical psychology, childhood and disability studies. Curti and Moreno (2010) have argued that boundaries and borders are nothing if not the different relational and durational articulations of bodies and spaces. These entangled boundaries include borders between parent and child; culture and body; school, family and child.Through analysing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…However, delivering this equitably would require additional professionals and risk diverting scarce resources from more pressing needs. Goodley & Runswick-Cole (2015) argued that people with all types of disabilities need solidarity in order to resist manipulation by the pharmaceutical trade and powerful "psy" professionals. Dedifferentiation has supported development of the Disability Rights Movement as a collective that can challenge oppressive structures.…”
Section: Evidence About Advantages Of Dedifferentiationmentioning
confidence: 99%
“…However, delivering this equitably would require additional professionals and risk diverting scarce resources from more pressing needs. Goodley & Runswick-Cole (2015) argued that people with all types of disabilities need solidarity in order to resist manipulation by the pharmaceutical trade and powerful "psy" professionals. Dedifferentiation has supported development of the Disability Rights Movement as a collective that can challenge oppressive structures.…”
Section: Evidence About Advantages Of Dedifferentiationmentioning
confidence: 99%
“…Qualitative research has been further championed for "giving a voice" to individuals or groups who are often under-acknowledged or otherwise marginalized (both in research and society more broadly). Examples of such research can be found across a range of fields include feminist studies (Belford & Lahiri-Roy, 2018;Haigwood, 2012), disability studies (Goodley & Runswick-Cole, 2015;Liddiard et al, 2018) and race studies (Chang, 2013;Louis et al, 2016).…”
Section: Children's Voices In Qualitative Researchmentioning
confidence: 99%
“…The traditional narrative of crisis initiated by a child' s disability has overshadowed mediating factors and has failed to address the lack of appropriate support available to families of disabled children (Raina et al, 2005). In fact, emerging evidence indicates that some parents experience enrichment because of their child' s disability, report value in facing adversity and learning to advocate as a family and appreciate their involvement in the disability community (Goodley & Cole, 2015). Scorgie and colleagues (2004) developed a model of resilience and transformational outcomes in which the lives of parents are initially disrupted and disoriented by a child' s disability, as their worldview and beliefs are challenged.…”
Section: Disabled Children and Their Familiesmentioning
confidence: 99%